Odpowiedź :
Odpowiedź:
a) 4a + 6= 70- 6a
4a+6a=70-6
10a=64/:10
a=6,4
b) 33- (12x + 6) = 6x
33-12x-6=6x
-12x-6x=-27
-18x=-27/:-18
x=3/2
c) 5 (2a + 7) = 4 (13 - 6a)
10a+35=52-24a
10a+24a=52-35
34a=17/:34
a=1/2
d) 35 +11x/6 = 2x/*6
210+11x=12x
11x-12x=-210
-1x=-210/:(-1)
x=210
Szczegółowe wyjaśnienie:
Odpowiedź:
siema
Szczegółowe wyjaśnienie:
a) 4a+6=70-6a |-6
4a=64-6a |+6a
10a=64 |:10
a=6,4
b) 33- (12x +6)=6x
33-12x+6=6x |-33
-12x+6=6x-33 |-6
-12x= 6x-39 |-6x
-18x=39 |:(-18)
x=2,2
c)5(2a+7)=4(13-6a)
10a+35=52-24a |-35
10a=18-24a |+24a
34a=18 |:34
a=0,53
d) 35+11x/6=2 | *6
35+11x=12 |-35
11x= -23
Myślę, że pomogłem... :)